Las actividades lúdicas como estrategia metodológica, en los estudiantes de tercero de básica “A” de la Unidad Educativa Hispanoamérica de la ciudad de Riobamba en el año lectivo 2023-2024. - Cubiña Velata, Yesenia Elizabeth (2024)
The focus on recreational activities is based on play as a natural form of learning that integrates cognitive, social and emotional aspects that promote the comprehensive development of children. By playing, students not only have fun, but also develop cognitive, social and emotional skills. In the context, it was observed that these activities helped children improve their concentration, motivation and participation in class. In the Hispanic American Educational Unit, the use of recreational activities has been implemented as methodological strategies for third grade students during the 2023-2024 school year. The objective is to improve the teaching-learning process through the use of play and fun as pedagogical tools. The study focuses on answering specific questions, the ones that include the evaluation of the execution of recreational activities by teachers, the identification of methodological strategies that strengthen meaningful learning, and the definition of specific activities that can be successfully applied. The general and specific objectives of the research focus on determining how recreational activities can strengthen student learning. A mixed methodological approach is used that combines qualitative and quantitative analysis. The research design is transversal, with a descriptive case study, focused on a specific population of 23 students and 10 teachers in the third year of basic education at the institution in the period 2023-2024. This allows for a detailed and representative evaluation at a specific point in time, basing recommendations on solid and direct evidence. In summary, the research seeks to validate the effectiveness of recreational activities as an innovative educational method, with the potential to positively influence the learning process of the students of the Hispanic American Educational Unit.